Interfaith Engagement in Milwaukee: A Brief History of Christian-Muslim Dialogue: oleh Irfan A. Omar and Kaitlyn C. Daly (eds.) - Hans A. Harmakaputra (Asosiasi Teolog Indonesia, 2021)
This is a book review of Interfaith Engagement in Milwaukee: A Brief History of Christian-Muslim Dialogue